1999
DOI: 10.1080/108107399126869
|View full text |Cite
|
Sign up to set email alerts
|

Health Communication and Consumer Behavior on Meat in Belgium: From BSE until Dioxin

Abstract: This article focuses on the impact of mass media meat-health information on consumer perception, attitude, and behavior toward fresh meat in Belgium. In a situation similar to that which occurred in most other European countries, Belgian fresh meat consumption fell considerably during 1995-1999. A multitude of messages linking meat consumption to human health risks were reported by mass media. Bovine Spongiform Encephalopathy (BSE) since 1996 and dioxin in 1999 constituted the major issues. Empirical research,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(8 citation statements)
references
References 18 publications
(22 reference statements)
2
5
0
Order By: Relevance
“…In line with previous research, the primary care nurses who participated in this study reported that patients could be heavily influenced by controversial health stories from various forms of mass media such as the Internet, print media and television [3,30,31]. This not only impacted on patients’ judgments about some healthcare practices, but also impinged on primary care nurses’ workloads as they reported having to spend an increasing amount of time discussing the latest news stories with patients, especially when controversies occurred.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In line with previous research, the primary care nurses who participated in this study reported that patients could be heavily influenced by controversial health stories from various forms of mass media such as the Internet, print media and television [3,30,31]. This not only impacted on patients’ judgments about some healthcare practices, but also impinged on primary care nurses’ workloads as they reported having to spend an increasing amount of time discussing the latest news stories with patients, especially when controversies occurred.…”
Section: Discussionsupporting
confidence: 75%
“…However, some research indicates that, especially during high levels of publicity, health stories in the media can be more influential than interpersonal sources [30]. This indicates that providing accurate and up-to-date information to counterbalance inaccuracies in media stories may assist health professionals to confidently discuss and share best evidence with patients, while taking account of their personal views and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…The news media are also a major arena in which the potential benefits and detriments related to nuclear energy are debated. There are numerous studies that show that the way risks are covered by the mass media has a significant impact on public opinion, risk perception, and public acceptance of risky technologies (Ashworth, 2009;Kasperson et al, 1988;Kristiansen & Bonfadelli, 2014;Verbeke, Viaene, & Guiot, 1999;Wahlberg & Sjoberg, 2000). Therefore, there is a strong interest among communication science scholars in the risk coverage of nuclear energy by the news media.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important concern for the agricultural industry, as the media are an important source of risk information for producers (Chiu, Cheyney, Ramirez, & Gerr, 2015). Risk literature has established that the media stories increase the "availability" of risk information and images for public audiences (Tversky & Kahneman, 1974;McComas, 2006), and along with interpersonal communication, journalists can amplify risk and safety information (Verbeke, Viaene, & Guiot, 1999;Southwell & Yzer, 2007). Neuwirth, Dunwoody, and Griffin (2000) found that risk information in news media encouraged individuals to seek additional information and take protective actions.…”
Section: Media As a Source Of Safety Informationmentioning
confidence: 99%